The Role of Genetic Variants (rs869109213 and rs2070744) Of the eNOS Gene and BglII in the α2 Subunit of the α2β1 Integrin Gene in Diabetic Retinopathy in a Tunisian Population. (4th July 2019) - Midani, Fatma; Ben Amor, Zohra; El Afrit, Mohamed Ali; Kallel, Amani; Feki, Moncef; Soualmia, Hayet
ABSTRACT: Purpose : In this study, we investigated the association of two polymorphisms (rs869109213 and rs2070744) in the eNOS gene and one polymorphism Bgl II in the α2 β1 integrin gene ( ITGA2 ) with the risk of diabetic retinopathy (DR) in a Tunisian population. Methods : The study investigated of 110 type 2 diabetes mellitus (T2DM) and 127 DR patients. The genotypes of the eNOS 4b/4a (rs869109213) and −786T/C (rs2070744) polymorphisms and of the Bgl II polymorphism of ITGA2 were studied using the PCR or PCR-RFLP method. Results : The genotype distributions of the two polymorphisms in eNOS 4b4a and eNOS (−786T/C) were significantly different between T2DM and DR patients ( p < .004 and p = .033, respectively). These polymorphisms were associated with the risk of DR (OR = 2.65, 95%CI [1.45–4.84], p = .002) for the eNOS 4b4a genotype and (OR = 2.43, 95%CI [1.06 − 5.56], p = .036) for the CC genotype of the eNOS gene (−786T/C). Similarly, the genotype distribution of the Bgl II polymorphism was significantly different between the two groups studied ( p = .037). This polymorphism was associated with an increased risk of DR (OR = 4.03, 95% CI [1.17 − 7.85], p = .022) for Bgl II(+/+). Conclusion : The present study suggests that the polymorphisms 4b4a and −786T/C in the eNOS gene might be associated with DR. In addition, the Bgl II polymorphism in the ITGA2 gene was a risk factor for DR.